2014
DOI: 10.3758/s13423-014-0769-0
|View full text |Cite
|
Sign up to set email alerts
|

Judging the familiarity of strangers: does the context matter?

Abstract: Context affects face recognition, with people more likely to recognize an acquaintance when that person is encountered in an expected and familiar place. However, we demonstrate that a familiar context can also incorrectly lead to feeling that a stranger is known. More specifically, we asked whether a familiar place can increase the belief that a stranger has been encountered outside of the experimental context (e.g., in the news or in real life). Novel faces were paired with novel places, famous places (landm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Steblay, Dysart, & Wells, 2011), and some types of facial composite creation systems involve asking the eyewitness to recognise the face that most resembles the suspect amongst several alternatives (Frowd 2012;Solomon, Gibson, & Mist, 2013). Although our study did not investigate face recognition biases due to distractor familiarity, other studies have shown that presenting unfamiliar faces on a familiar background can cause people to falsely attribute memory signals from the background to the face (Deffler, Brown, & Marsh, 2014;Gruppuso, Lindsay, & Masson, 2007). Similar misattributions of familiarity may also occur between multiple faces that are simultaneously presented (Bower & Karlin, 1974), and such biases may be more likely in populations that are particularly susceptible to distraction, such as those with impaired attentional control (Engle, 2002), which likely includes older adults (Anderson et al, 2011;Campbell, Hasher, & Thomas, 2010;De Fockert, Ramchurn, Van Velzen, Bergström, & Bunce, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Steblay, Dysart, & Wells, 2011), and some types of facial composite creation systems involve asking the eyewitness to recognise the face that most resembles the suspect amongst several alternatives (Frowd 2012;Solomon, Gibson, & Mist, 2013). Although our study did not investigate face recognition biases due to distractor familiarity, other studies have shown that presenting unfamiliar faces on a familiar background can cause people to falsely attribute memory signals from the background to the face (Deffler, Brown, & Marsh, 2014;Gruppuso, Lindsay, & Masson, 2007). Similar misattributions of familiarity may also occur between multiple faces that are simultaneously presented (Bower & Karlin, 1974), and such biases may be more likely in populations that are particularly susceptible to distraction, such as those with impaired attentional control (Engle, 2002), which likely includes older adults (Anderson et al, 2011;Campbell, Hasher, & Thomas, 2010;De Fockert, Ramchurn, Van Velzen, Bergström, & Bunce, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…All were frontal pictures, measured 9 cm 2 , and were converted into black and white (when necessary) using Adobe Photoshop CC (Adobe Systems Incorporated, 2014). Given that context affects face recognition (Deffler et al, 2015) and our objective was to access the recognition of faces regardless of the context, the presentation of faces occurred in a background without any distinguishable features.…”
Section: Methodsmentioning
confidence: 99%